Konsolidasi Tanah terhadap Relokasi Korban Pasca Erupsi Gunung Semeru 2021 dalam Kerangka Kepastian Hukum Hak Atas Tanah - Huda, Miftahul; Suarda, I Gede Widhiana; Setyawan, Fendi (Wajah Hukum, 2024)
As the year 2021 came to a close, Mount Semeru, which is situated in the Malang and Lumajang districts, erupted, bringing with it hot clouds and lava avalanches that destroyed nearby homes and property, erasing the lines separating the land owned by the locals. Normative-empirical legal research was the research methodology utilised to complete this thesis. The socio-legal approach, the statute approach, and the conceptual approach are the three methods used in this study. All three methods use empirical data from observations and interviews with people to do research. The implementation of land consolidation for relocation following the Semeru eruption, legal certainty regarding land ownership rights for the residential relocation of Mount Semeru eruption victims in 2021, and the idea of land consolidation for the relocation of Semeru eruption victims are the main areas of concern in this research. The concept of land consolidation is in accordance with the regulations of the Minister of Agrarian Affairs and Spatial Planning/head of the national land agency of the Republic of Indonesia number 12 of 2019 regarding land consolidation. As a consequence of land consolidation, the findings of this study will guarantee that the land rights of those affected by the Mount Semeru eruption are legally guaranteed.